Possible contribution of chronobiology to cardiovascular health - Sato, Miho; Matsuo, Takahiro; Atmore, Henry; Akashi, Makoto (Frontiers in Physiology, 2014)
The daily variations found in many aspects of physiology are collectively known as circadian rhythm (from “circa” meaning “about” and “dien” meaning “day”). Circadian oscillation in clock gene expression can generate quantitative or functional variations of the molecules directly involved in many physiological functions. This paper reviews the molecular mechanisms of the circadian clock, the transmission of circadian effects to cardiovascular functions, and the effects of circadian dysfunction on cardiovascular diseases. An evaluation of the operation of the internal clock is needed in clinical settings and will be an effective tool in the diagnosis of circadian rhythm disorders. Towards this end, we introduce a novel non-invasive method for assessing circadian time-regulation in human beings through the utilization of hair follicle cells.